Basic Immunization Program Coverage of Minimum Service Standards (MSS) in Raja Aligas, Huta Bayu Raja District - Shofian Syarifuddin (PT Inovasi Pratama Internasional, 2023)
Immunization is an effective way to provide immunity, especially to someone who is healthy, with the main goal of reducing morbidity and mortality due to various diseases that can be prevented by immunization. One of them is measles, which often attacks children under the age of five. The research objective was to determine the results of the basic immunization program coverage against the Minimum Immunization Service Standards. The research design used in this study is a descriptive study design. The number of samples in this study from the Raja Maligas in Silakkidir Village, Huta Bayu Raja District, Simalungun Regency was 47 people. with the sampling technique in this study using total sampling. Data analysis used is descriptive analysis. The results of the research on immunization coverage at Raja Maligas in Silakkidir Village showed that the majority of babies had received basic immunization HB 0, DPT/HB 1, DPT/HB 2, DPT/HB 3, POLIO 1, POLIO 2, POLIO 3 as many as 47 people (100% ) and a minority of infants received basic immunizations for BCG, POLIO 4, and MEASLES, respectively 95.7%, 97.9% and 95.7%. From the results of this study it is known that the coverage of the basic immunization program at the Raja Maligas has reached the Immunization Minimum Service Standards (SPM) in accordance with those set by the Government. So it is recommended that immunization officers at the health center continue to provide complete basic immunization services to every baby before the age of 1 year.